Antiplatelet and Anticoagulation Therapy in Structural Heart Disease Interventions Beyond TAVI - Vavuranakis, Manolis; Boudoulas, Konstantinos D.; Katsarou, Ourania; Vrachatis, Dimitrios A.; Kalogeras, Konstantinos I.; Papaioannou, Theodore G.; Siasos, Gerasimos; Oikonomou, Evangelos; Lazaros, George; Vavuranakis, Michael-Andreas; Deftereos, Spyridon; Tousoulis, Dimitrios (Current Pharmaceutical Design, 2017)
Transcatheter interventions for structural heart disease represent an emerging field in interventional cardiology. Undoubtedly, there is an absolute necessity for antiplatelet and/or anticoagulation treatment prior, during and post such interventions. However, currently administered regimens are mainly based in expert consensus recommendations. In the present review we aim to summarize data regarding anti platelet and/or anticoagulation treatment in the following transcatheter structural heart interventions: left atrial appendage closure, atrial septal defect closure, patent foramen oval closure, paravalvular leak closure.
Keywords: warfarin